ADP-Dependent Kinases From the Archaeal Order Methanosarcinales Adapt to Salt by a Non-canonical Evolutionarily Conserved Strategy - Gonzalez-Ordenes, Felipe; Cea, Pablo A.; Fuentes-Ugarte, Nicolás; Muñoz, Sebastián M.; Zamora, Ricardo A.; Leonardo, Diego; Garratt, Richard C.; Castro-Fernandez, Victor; Guixé, Victoria (Frontiers in Microbiology, 2018)
Halophilic organisms inhabit hypersaline environments where the extreme ionic conditions and osmotic pressure have driven the evolution of molecular adaptation mechanisms. Understanding such mechanisms is limited by the common difficulties encountered in cultivating such organisms. Within the Euryarchaeota, for example, only the Halobacteria and the order Methanosarcinales include readily cultivable halophilic species. Furthermore, only the former have been extensively studied in terms of their component proteins. Here, in order to redress this imbalance, we investigate the halophilic adaptation of glycolytic enzymes from the ADP-dependent phosphofructokinase/glucokinase family (ADP-PFK/GK) derived from organisms of the order Methanosarcinales. Structural analysis of proteins from non-halophilic and halophilic Methanosarcinales shows an almost identical composition and distribution of amino acids on both the surface and within the core. However, these differ from those observed in Halobacteria or Eukarya. Proteins from Methanosarcinales display a remarkable increase in surface lysine content and have no reduction to the hydrophobic core, contrary to the features ubiquitously observed in Halobacteria and which are thought to be the main features responsible for their halophilic properties. Biochemical characterization of recombinant ADP-PFK/GK from M. evestigatum (halophilic), and M. mazei (non-halophilic) shows the activity of both these extant enzymes to be only moderately inhibited by salt. Nonetheless, its activity over time is notoriously stabilized by salt. Furthermore, glycine betaine has a protective effect against KCl inhibition and enhances the thermal stability of both enzymes. The resurrection of the last common ancestor of ADP-PFK/GK from Methanosarcinales shows that the ancestral enzyme displays an extremely high salt tolerance and thermal stability. Structure determination of the ancestral protein reveals unique traits such as an increase in the Lys and Glu content at the protein surface and yet no reduction to the volume of the hydrophobic core. Our results suggest that the halophilic character is an ancient trait in the evolution of this protein family and that proteins from Methanosarcinales have adapted to highly saline environments by a non-canonical strategy, different from that currently proposed for Halobacteria. These results open up new avenues for the search and development of novel salt tolerant biocatalysts.